Property rights, optimal public enforcement, and growth - Andreas Irmen; Johanna Kuehnel (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study the link between public enforcement of property rights, innovation investments, and economic growth in an endogenous growth framework with an expanding set of product varieties. We find that a government may assure positive equilibrium growth through public employment in the enforcement of property rights, if the economic environment is sufficiently favorable to growth and/or public enforcement is sufficiently effective. However, in terms of welfare an equilibrium path without property rights protection and growth might be preferable. In this case the enforcement of property rights involves too much reallocation of labor from production and research towards the public sector.
Keywords: O10; H11; D23; 330; technological change; economic development; property rights; public employment; Eigentumsrecht; Rechtsdurchsetzung; Innovation; Neue Wachstumstheorie; Öffentliche Verwaltung; Wohlfahrtseffekt; Theorie